A sanctuary from everyday life: rheumatology patients' experiences of in-patient multidisciplinary rehabilitation – a qualitative study. Issue 10 (8th May 2022) - Stauner, Maria; Primdahl, Jette
Abstract: Purpose: To explore how rheumatology patients experience the personal impact of an inpatient rehabilitation stay and to elucidate the impact of contextual factors on the outcome. Methods: Exploratory qualitative individual interviews were conducted with 15 rheumatology patients (73% female) who had completed a two-week inpatient rehabilitation stay. Data collection, analysis and interpretation of data were performed within a phenomenological-hermeneutic framework inspired by Paul Ricoeur's interpretative philosophy. Results: The analysis derived one core theme, A sanctuary from everyday life, and five subthemes: (1) Being seen, heard and acknowledged as an equal and whole person; (2) Professional care and compassion ; (3) Social relations and interactions between patients ; (4) Individual rehabilitation, but challenges regarding shared decision making; and (5) Rehabilitation as a personal process but problems with coherence and transferability of learning to everyday life . Conclusion: Patients experience inpatient rehabilitation as a sanctuary, in the following three ways; through individually planned multidisciplinary interventions at the hospital; recognition and compassion from the multidisciplinary staff and through social relationships and interactions with fellow patients. There is a need for improved coordination across primary and secondary health care, to ease coherence and transfer of learning to the patients' everyday lives. IMPLICATIONS FOR REHABILITATION: Patients can find peace and energy to care for themselves because they are away from everyday life when admitted for inpatient multidisciplinary rehabilitation. Patients need to be prepared for shared decision-making in order to be able to participate in formulating personal and meaningful goals for rehabilitation. There is a need for awareness of organisational and life transitions, to secure transfer of elements from the rehabilitation stay to the patient's everyday life. Rehabilitation professionals should be aware of the significance of fellow patients and facilitate and support the patient-patient relationships.